Synthesis, Anti-Inflammatory Activity, and Docking Simulation of a Novel Styryl Quinolinium Derivative - Mina Todorova; Rumyana Bakalska; Mehran Feizi-Dehnayebi; Ghodsi Mohammadi Ziarani; Mina Pencheva; Kirila Stojnova; Miglena Milusheva; Paraskev Nedialkov; Emiliya Cherneva; Tsonko Kolev; Stoyanka Nikolova (Applied Sciences)
Stilbenes, like resveratrol, are natural small molecules with several applications in the treatment of chronic illnesses, diabetes, and neurological and cardiovascular conditions. Considering the molecular structure of stilbenes and the biological activities of resveratrol, we investigated the synthesis and biological activity of a novel styryl quinolinium (SQ) derivative. The SQ was synthesized using the alkylation of lepidine and methyl 4-methylbenzenesulfonate and further Knoevenagel condensation with 2-hydroxy naphthaldehyde. Its structure was determined using NMR, IR, Raman, UV-Vis, and MS. The current trend of research has shifted toward the synthesis of novel SQ as resveratrol’s analog. Therefore, its anti-inflammatory and antioxidant activities were evaluated. The compound exerted very good anti-inflammatory effects in preventing albumin denaturation, which were confirmed by ex vivo immunohistochemical studies. Density functional theory (DFT) analyses were conducted on the SQ structure to gain detailed insights into its active sites, energy gap, quantum properties, and electronic behavior. The biological evaluation of the compound was completed, assessing its antioxidant potential using DPPH radical scavenging assay. In addition, molecular docking simulations were utilized to assess the SQ compound’s potential inhibitory effect on human serum albumin (HSA).